Strategi Gereja Memaksimalkan Tri Panggilan Gereja Pada Masa Pandemi Covid-19 - Eva Inriani (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2021)
The Covid-18 pandemic is a global problem affecting various sectors of life, including the church. The church as a fellowship og God`s people must limit itself to direct interactions between members of its congregation, in ordet to prevent the spread of Covid-19. This massif social distancing also affects the manifesting of Three Church Calls: Witnessing, Allying and Serving. In this case that the church must implement the right strategies to respons the challenges of the pandemic. This paper aims to examine the strategies of the churches in Palangka Raya in an effort to maximize the manifesting of Three Church Calls during the Covid-19 pandemic.This research used a qualitative approach, with a descriptive type of research.Through this research, it can be concluded that the church has intelligently attempted to answer the challenges during the Covid pandemic, by maximizing service through the digital church model.The church maximizes the manifesting of Three Church Calls by utilizing various social media platforms available in the digital era. The Covid-19 pandemic has put the church in challenges, but this event has become a momentum for the church to reflect again on God`s calling, to preach the gospel, and at the same time the church is encouraged to develop in its ministry, in line with the challenges and development of the times.